Gabapentin-Induced Choreoathetosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Two institutionalized, severely retarded adults, aged 42 and 41, with intractable epilepsy, developed choreoathetosis within 14 days when gabapentin in dosages of 1200 to 1800 mg/d were added as adjunctive therapy to valproic acid or phenytoin, in a report from University of Texas Southwestern Medical Center, Dallas, and Denton State School, Texas Mental Health and MR System.